Systematics and cryptic diversification of Leptodactylus frogs in the Brazilian campo rupestre - Carvalho, Thiago R. [UNESP]; Seger, Karin R.; Magalhaes, Felipe M.; Lourenco, Luciana B.; Haddad, Celio F. B. [UNESP] (Wiley-Blackwell, 2020)
The campo rupestre is a unique mountaintop ecosystem in eastern South America, recognised for its endemism and as ecological refugia for plant and animal taxa. Multiple clades of frogs are represented in the Brazilian campo rupestre. One such case is four species of the Leptodactylus fuscus group, three of which are endemic to specific mountain ranges (Leptodactylus camaquara, Leptodactylus oreomantis and Leptodactylus tapiti) and one that is more widespread across different mountain ranges (Leptodactylus cunicularius). In this study, we conducted a phylogenetic analysis of the clade containing the four Leptodactylus species endemic to the campo rupestre ecosystem and explored the biogeographic scenarios of origin and diversification of these montane frogs. The origin and early diversification of this frog clade took place in the Espinhaco Mountain Range (EMR) in the Miocene. This was followed by successive dispersal events to other mountain ranges in a circular pathway and subsequent rapid lineage diversification during the Plio-Pleistocene transition and early Pleistocene. The diversification of this anuran clade was likely triggered by the Pleistocene climatic oscillations and culminated in the return of one of the montane species to the EMR. Contrasting patterns of phenotypic and genetic divergence indicate cryptic speciation in these frogs unaccompanied by phenotypic disparity. A phenotypically cryptic but highly divergent genetic lineage was found to represent a distinct evolutionary unit in the Northern EMR, described here as a new species (Leptodactylus avivoca sp. n.). The circular dispersal pathway in this frog clade revealed a unique diversification pattern among vertebrates endemic to the Brazilian campo rupestre.
Keywords: dispersal; endemism; Espinhaç o Mountain Range; Quaternary climatic oscillations; rupestrian grasslands; speciation